Business English for Success - McLean, Scott (Open textbook library., 2011)
Business English for Success is a creative solution to a common challenge across Business Communication courses: Business English or Business Presentations? Some classes place an equal emphasis on oral and written communication. If that's the case for you check out our text Business Communication for Success. If, however, your class places the emphasis squarely on written communication and writing proficiency, then Business English for Success is for you. Business English for Success provides instruction in steps, builds writing, reading, and critical thinking, and combines comprehensive grammar review with an introduction to paragraph writing and composition. This step-by-step approach provides a clear path to student-centered learning. A wide range of writing levels and abilities are addressed, helping each student prepare for the next writing or university course. The text opens with a discussion on the sentence and then breaks it down into its elemental components, before reconstructing them into effective sentences, paragraphs, and larger assignments. Then, starting in Chapter 9: Effective Business Writing, the discussion applies lessons learned from the previous foundational chapters into common business issues and applications. From paraphrasing and plagiarism to style to the research process, the expectations increase as several common business documents are presented, including text messages and e-mail, memorandums and letters, the business proposal, business report, resume, and the sales message. This textbook has been used in classes at:Arizona Western College, Hostos Community College, Virginia State University, Truckee Meadows Community College, San Jose State University, Concordia University - Irvine, University New Brunswick - Fredericton, Cerritos College, University of Houston - Downtown, Flat World Knowledge University, A-C Central High School, University of The People, Truckee Meadows Community College, Danville Community High School